ZAKAT SEBAGAI INSTRUMEN SOSIOEKONOMI PADA MASA RASULULLAH SAW - La Abdul Zayl; Muammar W. Maruapey; Arizal Hamizar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The majority of Muslims' understanding of zakat is still limited to the normative dimension. Zakat tends to be understood in a legalistic way and seems to be separated from the main mission of zakat, namely the economic welfare of Muslims. This article aims to describe zakat as a socio-economic instrument during the time of the Prophet Muhammad. Methodologically, this article uses the library research method with data collection techniques through articles, books and other supporting documents. This article confirms that the historicity of zakat is closely related to Islamic efforts to achieve economic balance in society. Initially, this zakat collection was a criticism of economic inequality at that time and therefore, within the minimum limit of a person's wealth reaching 85 grams, he was obliged to pay zakat. The meaning is that the zakat instrument is presented for economic equality and pays attention to eight social groups from economic and theological aspects. The article recommends that contemporary zakat governance pay attention to aspects of sustainable economic improvement for zakat mustahik.